Antonuc Е. V. Аbout 2 approaches to nicknames semantics studying - Antonuc Е. V. (Philological Treatises, 2020)
The article provides deep insight into problems of nicknames semantics. Special attention is paid to the process of semantics of nicknames as language sign. The meaning of componential analysis is disclosed. The author provides the designation of nicknames meaning.